Manajemen Kearsipan Di Kantor Desa Tampiala Kecamatan Dampal Selatan Kabupaten Tolitoli - Regita, Sri; Suasa; Farista, Gita (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2024)
This research aims to determine how archival manangement is in the Tampiala village office. The basics of this research is observation and this type of research was conducted at the Tampiala village office South Dampal sub-district Tolitoli district, which examines archival management. In terms of implementation, each person in charge has an important specific task. So that complete supporting facilities are needed in carrying out their duties and obligations. To increase the sense of respontibility in completing tasks and work and the trust given. In this study reseaerches involved 5 (five) informants namely the Tampiala village head, Tampiala village Secretary, planning section, welfare sections, and government section. In conducting research, the author uses the theory of sularso mulyono which refers to 3 (three) aspects namely receiving letters, storing or placing archives, and finding back archives. Based on the results of the research obtained, it can be cocluded that arcival management at the Tampiala Village Office South Dampal district Tolitoli Regency in the aspect of receiving letters has been running well, but three are several aspect that need to be addresed, such as in the aspects of archive storage or placement and archive retreval that need to be addresed, including storage because the facilities and infrastructure are not sufficient, for example, sufficient cabinets, so there are several archives on the table, to use boxes to store archives.And the retreval of archives has not been running effectively where there are no experts in managing in the field of archives, so it needs to be understood that the management of archives at the Tampiala village office south Dampal District tolitoli regency requires a long time and delays in finding archives.